Capnography-assisted airway management by awake blind nasal intubation in maxillofacial surgeries: An observational study - Kokate, Minal; Vikram Kokate,; Gaurav Dubey,; Vijaya Borkar, (Asian Journal of Medical Sciences, 2024)
Background: Maxillofacial surgery patients frequently pose challenges to airway management due to anatomical and functional constraints. While fiber-optic-aided nasotracheal intubation is considered the gold standard, not all medical facilities have access to fiber-optic bronchoscopes, particularly in low-resource settings. In such situations, awake nasal tracheal intubation is often the safest approach for managing patients with known or suspected difficult airways. Aims and Objectives: (1) To assess the technique of capnography-assisted airway management by awake blind nasal intubation (ABNI) in maxillofacial surgeries. (2) To find out any complications encountered by the technique of capnography-assisted airway management by ABNI in maxillofacial surgeries. Materials and Methods: 40 patients undergoing various maxillofacial surgeries and in whom blind nasotracheal intubation was attempted were included in this study. The institutional ethical committee approved the study, and informed consent was obtained from all the patients. The number of attempts for ABNI, successful versus failed ABNI, and complications encountered were studied. SSPS 21.0 software was used for statistical analysis. Results: There were 23 (57.50%) males and 17 (42.50%) females. There was a male preponderance, with the M: F ratio being 1:0.73. The mean age of the patients was 40.97±8.92 years. In 36 (90%) of the patients, the intubation could be successfully done. In 19 (47.50%) patients, blind nasal intubation was successfully done in the first attempt; 2 attempts were required in 15 (37.50%) patients, and 3 attempts were required in 2 (5%) patients. Epistaxis (10%) and sore throats (7.5%) were the most common complications in the studied cases. Conclusion: Capnography-assisted ABNI is an effective technique for airway control in patients undergoing maxillofacial surgeries with an acceptable complication rate.